Drying and color in punamuña leaves (Satureja boliviana) - Choque Quispe, David (2020)
Drying allows water to be removed and food to be preserved, however, this operation can degrade color. Punamuña leaves are aromatic and used for medicinal purposes in the Peruvian Andes. This research aimed to determine and model the drying kinetics, the diffusivity coefficient (Def), the activation energy (Ea), and the color of punamuña leaves. A horizontal dryer was used at 40, 50, and 60 °C and airspeed of 1.0 and 0.5 m / s; drying kinetics was modeled with 10 models. Def was determined with the Fick equation, Ea with the Arrhenius equation; the color was determined in the L* a* b* space. It was found that the triple exponential model with six parameters better represented the drying kinetics (R2 > 99.73 and E<3.04%); Def increased with temperature and air velocity. Ea was found between 43.62 to 44.52 kJ/mol for speeds of 1.0 to 0.5 m/s respectively; L* and a*/b* decreased, the color difference ΔE * increased with increasing temperature and lower air velocity.